Analysis of business opportunities of waqf land at yayasan attaqwa using smart and ahp - Hilaliah, Lia; Kusumo Bintoro, Bambang Purwoko (The Indonesian Journal of Business Administration, 2018)
Abstract. This research begins with a simple question: how to utilize waqf land in order to benefit the Nazir and the community?. The Indonesian Waqf Board notes that the number of wakaf land in Indonesia reaches 4,359,443,170 m2 managed by wakif, one of the wakif is the Attaqwa Foundation. The Attaqwa Foundation established in 1950 is engaged in education and social affairs, owning land assets of 910,629 m2, and 22% of the total land is waqf land. As a Nazir, the Attaqwa Foundation, through the Waqf Board of Attaqwa Foundation, is obliged to organize, maintain and optimize the waqf land owned for the benefit of the ummah. This research tries to map the business opportunities that can be taken to develop the potential of existing waqf land and choose the best one by the decision maker. This research divides the benefit into two: economic benefit and social benefit, which then divided into six criteria: trust, job creation, sales, social assistance, and sustainability of physical infrastructure. From observations and interviews, there are four business options that can be developed, namely cooperation or mart, sports center, tempeh factories, and cultivation of catfish. By conducting SMART and AHP analysis, this study yields the conclusion that the highest benefits business option is Mart. The advantages of Mart will eventually be returned to the community as the full beneficiaries of the utlization of waqf land carried out by the Waqf Board of Attaqwa Foundation.Keywords: waqf, nazir, Attaqwa, SMART, AHP